Biomarking and Induction of Apoptosis in Ovarian Cancer Using Bifunctional Polyethyleneimine-Caged Platinum Nanoclusters - Zhang, Mengjun; Yue, Haodi; Liu, Yuan; Li, Hao; Yin, Yue; Sun, Zhenxing; Cui, Ping; Li, Fei; Chen, Xiuwei; Huang, Xin (Frontiers in Oncology, 2022)
According to the 2020 GLOBOCAN Global Cancer Women's Cancer Data, ovarian cancer is the eighth most common tumor in humans. Still, its mortality rate ranks first among all gynecological tumors, with a 5-year survival rate of 30% to 50%. Widespread clinical use of platinum-based drugs has improved survival outcomes in patients with ovarian cancer, but organ toxicity and drug resistance hinder their anticancer effects. In particular, the resistance to platinum drugs is an important reason for ovarian cancer's high recurrence rate and mortality. With the development of chemotherapeutic drugs synthesized by nanomaterials in the biomedical field, we developed bifunctional ultrafine polyethyleneimine caged platinum nanoclusters (PEI-Pt NCs) to improve the dilemma of platinum drugs. This study aimed to elucidate the antitumor effect of PEI-Pt NCs in OC. First, as observed by confocal microscopy, Pt NCs entered OC cells in a dose-dependent manner and accumulated on the surface of the nuclear membrane and in the nucleus. Subsequently, through cck8, ki-67 immunofluorescence, wound healing assay, transwell assay, clone formation assay, flow cytometry, tunel staining, and western blotting assay, it was confirmed that PEI-Pt NCs could inhibit the proliferation and migration and induce the apoptosis of ovarian cancer cells. PEI-Pt NCs can be used as fluorescent markers for systemic bioimaging of ovarian cancer, showing great potential in diagnosing and treating ovarian cancer, and making a specific contribution to solving the dilemma of platinum-based drug therapy for OC.